Advances in the visual analysis of social movements - Doerr, Nicole; Mattoni, Alice, 1978-; Teune, Simon (Bingley, U.K. : Emerald, 2013)
This special issue of Research in Social Movements, Conflicts and Change highlights the importance of visuals in the current study of social movements. It is indispensable reading as it introduces new analytical concepts and methodological frameworks for understanding visuals in social movements; combining cultural and political analysis in a fresh, unique and interdisciplinary way. The articles featured in this special issue examine visual expressions of social movements through case studies from across the globe; including: injustice symbols in the Egyptian uprising; contested images from anti-surveillance protests in Germany; gendered visualization of local activism; commemorative videos of activists in recent European protests; and images used in Australian movements against abortion. In the open section of the volume articles examine the work of renowned political science scholar Charles Tilly, and discuss classic concepts in social movement studies. Firstly, considering the concept of "repertoire of contention" in order to understand the use of distinct contentious performances in Latin America. Secondly, analyzing the role of "storytelling" in the construction of trust and blame in social movements.
"We are all Khaled Said" : visual injustice symbols in the Egyptian revolution, 2010-2011 / Thomas Olesen -- Bodies keying politics : a visual frame analysis of gendered local activism in France and Finland / Eeva Luhtakallio -- Images of surveillance : the contested and embedded visual language of anti-surveillance protests / Priska Daphi, Anja Lê, Peter Ullrich -- The emotional imperative of the visual : images of the fetus in contemporary Australian pro-life politics / Kirsty McLaren -- Protest movements and spectacles of death : from urban places to video spaces / Tina Askanius -- What we can do with visual analysis in social movement studies : some (self) reflections / Donatella della Porta -- The work stories do : Charles Tilly's legacy on the provision of reasons, storytelling, and trust in contentious performances / Marc W. Steinberg, Patricia Ewick -- Repertoires of contention and tactical choice in Latin America, 1981-1995 / James C. Franklin.
Print version record
Keywords: Social Science -- Research; Social Science -- Social Classes; Social Science -- General; Sociology; Revolutionary groups & movements; Social movements -- United States; Social movements; Persuasion (Psychology)